2023
DOI: 10.1039/d2nj04896e
|View full text |Cite
|
Sign up to set email alerts
|

An innovative hybrid biosorbent composed of nano ZnO and marine macro algae Jania rubens embedded in an alginate/PVA matrix: insights into Pb2+ removal in water

Abstract: Nanoparticles of zinc oxide (ZnO) combined with Jania rubens (JR) biosorbent have been embedded in a sodium alginate (SA)–polyvinyl alcohol (PVA) matrix. This hybrid biosorbent has been characterized by FTIR,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Algae have been found to be a potential multi-functional material due to their cell walls with functional groups such as carboxylate, amino, hydroxyl, and phosphate, which play a pivotal part in grafting, and adsorbing. 20 Here, we demonstrated that keratin and unmodified SP were crosslinked successfully to obtain keratin-seaweed hydrogels with megascopic porous networks. Compared with FK-2, the rough, fluffy, and relatively larger porous structure of FK-SP was observed (Fig.…”
mentioning
confidence: 86%
“…Algae have been found to be a potential multi-functional material due to their cell walls with functional groups such as carboxylate, amino, hydroxyl, and phosphate, which play a pivotal part in grafting, and adsorbing. 20 Here, we demonstrated that keratin and unmodified SP were crosslinked successfully to obtain keratin-seaweed hydrogels with megascopic porous networks. Compared with FK-2, the rough, fluffy, and relatively larger porous structure of FK-SP was observed (Fig.…”
mentioning
confidence: 86%